Oligomycin A enhances apoptotic effect of TRAIL through CHOP‐mediated death receptor 5 expression1. Issue 2 (15th November 2011) - He, Long; Jang, Jae Hyuk; Choi, Hyun Gil; Lee, Sun Mi; Nan, Mei Hua; Jeong, Sook Jung; Dong, Zigang; Kwon, Yong Tae; Lee, Kyung Sang; Lee, Ki Won; Chung, Jong Kyeong; Ahn, Jong Seog; et al.
Abstract Development of resistance to TNF‐related apoptosis‐inducing ligand (TRAIL) in tumor cells is one of the important problems in cancer treatment. Despite the previous report demonstrating that oligomycin suppressed TNF‐induced apoptosis, in our screening of small molecules enhancing cancer cell death to TRAIL, oligomycin A (OMA) was found to enhance TRAIL‐induced apoptosis in HeLa cells. CCAAT/enhancer‐binding protein homologous protein (CHOP) was found to directly bind to death receptor 5 (DR5) promoter through endoplasmic reticulum stress (ER‐stress) signaling and sensitize the cells to TRAIL. Among ER‐stress associated proteins, OMA triggered the inositol‐requiring enzyme 1 (IRE1) signaling pathway, leading to X‐binding protein 1 (XBP1) splicing, CHOP expression and DR5 upregulation. In contrast, small‐interfering RNA (siRNA) of CHOP reduced the number of apoptotic cells in response to the co‐treatment of TRAIL and OMA. Collectively, our data suggest that OMA enhances apoptotic death of cervical cancer cells to TRAIL through upregulation of CHOP‐mediated DR5 expression following ER‐stress. © 2011 Wiley Periodicals, Inc.